Acupuncture compares with Western medicine for climacteric depression - Hong, Quan Xiao; Hong, Ma; Ying, Li; Cai, Wu; Hua, Chen Xiu (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to assess the clinical efficacy and safety of acupuncture for climacteric depression. Two reviewers searched major databases independently. The quality assessment and data analysis were evaluated by Cochrane reviews 5.3.0. Seventeen clinical trials were included, contained 1,369 cases. Meta-analysis of acupuncture comparing with medicine showed that: a) Affective rate: [OR = 1.44, 95% CI (1.02, 2.04)], the difference had statistically significance; b) HAMA score : [MD = -2.12, 95% CI (-2.85, -1.40)], the difference had statistically significance; c) HAMD score: The difference of the 2nd week, 4th week, 6th week, 8th week, or 12th week was not statistically significant; d) Kupperman score: [MD = -5.05, 95% CI (-11.94, 1.84)] showed no statistical significance; e) Incidence of adverse events of acupuncture (2.7%) was significantly less than the control group (20%). In conclusion acupuncture will help to improve depressive symptoms of climacteric and decrease adverse reactions.